One‐Dimensional Arsenic Allotropes: Polymerization of Yellow Arsenic Inside Single‐Wall Carbon Nanotubes. (6th August 2018) - Hart, Martin; Chen, Ji; Michaelides, Angelos; Sella, Andrea; Shaffer, Milo S. P.; Salzmann, Christoph G.
Abstract: The pnictogen nanomaterials, including phosphorene and arsenene, display remarkable electronic and chemical properties. Yet, the structural diversity of these main group elements is still poorly explored. Here we fill single‐wall carbon nanotubes with elemental arsenic from the vapor phase. Using electron microscopy, we find chains of highly reactive As4 molecules as well as two new one‐dimensional allotropes of arsenic: a single‐stranded zig‐zag chain and a double‐stranded zig‐zag ladder. These linear structures are important intermediates between the gas‐phase clusters of arsenic and the extended sheets of arsenene. Raman spectroscopy indicates weak electronic interaction between the arsenic and the nanotubes which implies that the formation of the new allotropes is driven primarily by the geometry of the confinement. The relative stabilities of the new arsenic structures are estimated computationally. Band‐gap calculations predict that the insulating As4 chains become semiconducting, once converted to the zig‐zag ladder, and form a fully metallic allotrope of arsenic as the zig‐zag chain.